CO2 Adsorption: Experimental Investigation and CFD Reactor Model Validation. (30th October 2014) - Breault, Ronald W.; Shadle, Lawrence J.; Spenik, James L.; Huckaby, E. David
Abstract : The National Energy Technology Laboratory is investigating a new process for CO2 capture from large sources such as utility power generation facilities as an alternative to liquid amine based adsorption processes. Many of these advanced dry processes are based upon sorbents composed of supported polyamines. In this analysis, experiments have been conducted in a laboratory-scale fluidized bed reactor and compared to CFD reactor predictions using kinetics obtained from TGA tests. Batch experiments were conducted by flowing a mixture of CO2, H2 O, and N2 (simulated flue gas) through a fluidized bed of sorbent material. The exit gas composition time series data is compared to CFD simulations using a 3-dimensional nonisothermal reacting multiphase flow model. The effects of the gas flow rate, distributor design, and particle size are explored through the CFD simulations. It is shown that the time duration for CO2 adsorption decreased for an increase in the gas flow. Fluid bed hydrodynamics indicated that there were regions in the reactor where the inert FCC particles segregated and defluidized; without adversely affecting the capacity of the sorbent to adsorb CO2 . The details of the experimental facility and the model as well as the comparative analysis between the data and the simulation results are discussed.